Structural and dynamical properties of polyethylenimine in explicit water at different protonation states: a molecular dynamics study - Choudhury, Chandan Kumar; Roy, Sudip (Soft Matter, 2013)
PEI is a pH sensitive polymer which acts as a proton sponge in acidic conditions. Despite many experimental and theoretical efforts, a fundamental understanding of the structure and dynamics of linear PEI chains on the atomistic level at different protonation states in dilute solutions remains a topic of discussion. This report analyses the structural properties of PEI at different protonation states, which are representative of different pH, using all atomistic molecular dynamic simulations. The structural properties revealed that the polymer at high pH (basic medium) is highly coiled, while at low pH (strong acidic conditions) the chains are elongated. We studied the dynamics and ordering of water molecules that are part of the solvation shells of the PEI chains at different protonation states. We observe that the water molecules are ordered along the polymer backbone for a completely protonated PEI chain (i.e. in the case of acidic pH) and hop to the neighbouring solvation shell. The residence time and the self-diffusion of water molecules in the solvation shells and their activation barriers were also calculated and analysed further. We concluded the study by correlating the solvation shell water dynamics and the structure of the PEI chain at different protonation states.

Scalability of coarse-grained potentials generated from iterative boltzmann inversion forpolymers: case study on polycarbonates - Choudhury, Chandan Kumar; Carbone, Paola; Roy, Sudip (Macromolecular Theory and Simulations, 2016)
Using systematic coarse-grained (CG) techniques such as iterative Boltzmann inversion (IBI) is an efficient means to simulate high molecular weight polymer melts within reasonable computational time. One drawback of such an approach is however the need to carry out extensive atomistic simulations in order to extrapolate the necessary distributions to derive the inter and intrabead force field parameters. Here it is shown that it is possible to use atomistic simulations of relative short oligomers to develop the CG model for high molecular weight polymers. In particular for the specific case of polycarbonates, it is found that the structural properties (end-to-end distance, radius of gyration and their distributions) are similar irrespective of whether the CG potentials are derived from 5-mer or 10-mer melt systems. Dynamical properties of the CG systems are smoother and faster than the atomistic ones. Scaling factor, derived by overlapping the CG mean square displacement curves (obtained from different CG IBI potentials) over the atomistic ones, also scales the autocorrelation functions. A prediction of the dynamical scaling factor in the case of the unavailability of atomistic simulations is also discussed. The dynamical properties of the CG melts are modeled reasonably well by all the CG potentials derived from atomistic simulations of short oligomers.

Self-exfoliated guanidinium-based ionic covalent organic nanosheets (iCONs) - Mitra, Shouvik; Kandambeth, Sharath; Biswal, Bishnu P.; Khayum, Abdul M.; Choudhury, Chandan Kumar; Mehta, Mihir R.; Kaur, Gagandeep; Banerjee, Subhrashis; Prabhune, Asmita; Verma, Sandeep; Roy, Sudip; Kharul, Ulhas K.; et al. (Journal of the American Chemical Society, 2017)
Covalent organic nanosheets (CONs) have emerged as functional two-dimensional materials for versatile applications. Although pi-pi stacking between layers, hydrolytic instability, possible restacking prevents their exfoliation on to few thin layered CONs from crystalline porous polymers. We anticipated rational designing of a structure by intrinsic ionic linker could be the solution to produce self-exfoliated CONs without external stimuli. In an attempt to address this issue, we have synthesized three self-exfoliated guanidinium halide based ionic covalent organic nanosheets (iCONs) with antimicrobial property. Self-exfoliation phenomenon has been supported by molecular dynamics (MD) simulation as well. Intrinsic ionic guanidinium unit plays the pivotal role for both self-exfoliation and antibacterial property against both Gram-positive and Gram-negative bacteria. Using such iCONs, we have devised a Mixed matrix membrane which could be useful for antimicrobial coatings with plausible medical benefits.